HUBUNGAN PENGETAHUAN IBU DENGAN PEMBERIAN MP-ASI PADA BAYI USIA 0-6 BULAN DI POLINDES BILLA’AN KECAMATAN PROPPOKABUPATEN PAMEKASAN - Riqqah Mar’ati; Qurratul A’yun (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2021)
Complementary food to breast milk is food or drink given to babies aged 6-24 months to meet nutritional needs other than breast milk. Supplementary food or complementary feeding programs have been implemented in Indonesia with the hope of reaching 80%, but in this case it fulfills many things. According to the 2008 Ministry of Health's national data, there were 28.5% or 6 million undernourished toddlers because there were still many people who lacked knowledge about the importance of maintaining nutrition from infancy.The purpose of this study was to analyze the relationship between the level of knowledge of mothers about complementary foods and offering complementary foods at the age of 0-6 months.This type of research is analytical correlation with cross sectional design. The population is all mothers who have babies aged 0-6 months in Billa'an village. Sampling using a total sampling technique of 34 respondents. The independent variable is mother's knowledge, while the dependent variable is offering complementary foods to babies aged 0-6 months. The instruments used were questionnaires and KMS books.The results of the study of 34 obtained results as many as 3 respondents (8.82,%) who have knowledge of complementary foods and 27 respondents (79.4%) are not appropriate in giving complementary foods at the age of 0-6 months. The statistical test used is Chi-Square with a significant number a = 0.05, then it is obtained X2 count (14.008)> X2 table (5.991) so that Ho is rejected.From the results obtained, it can be ignored that there is a significant relationship between maternal knowledge and complementary feeding in infants aged 0–6 months. Therefore the need for mother's awareness to increase mother's knowledge in providing complementary breastfeeding on time or age, namely for babies aged 6 months so that it does not pose a risk because the function of the baby's digestive system is not optimal if given complementary feeding before the baby is 6 months old.